Gender Dysphoria, Eating Disorders and Body Image: An Overview - Milano, Walter; Ambrosio, Paola; Carizzone, Francesa; De Biasio, Valeria; Foggia, Giuseppina; Capasso, Anna (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: Gender dysphoria is a clinical condition in which a state of inner suffering, stress and anxiety is detected when biological sex and a person's gender identity do not coincide. People who identify themselves as transgender people are more vulnerable and may have higher rates of dissatisfaction with their bodies which are often associated with a disorderly diet in an attempt to change the bodily characteristics of the genus of birth and, conversely, to accentuate the characteristics of the desired sexual identity. Aim: The purpose of this work is to examine the association between dissatisfaction with one's own body and eating and weight disorders in people with gender dysphoria. Results: Gender dysphoria and eating disorders are characterized by a serious discomfort to the body and the body suffers in both conditions. The results of our study suggest that rates of pathological eating behaviors and symptoms related to a disordered diet are high in patients with gender dysphoria and that standard screening for these symptoms must be considered in both populations at the time of evaluation and during the course of the treatment. Conclusion: In light of this evidence, clinicians should always investigate issues related to sexuality and gender identity in patients with eating disorders, to develop more effective prevention measures and better strategies for therapeutic intervention.
Keywords: bulimia nervosa